PERAN GURU DALAM MENANAMKAN KARAKTERI DISIPLIN SISWA DI SEKOLAH DASAR NEGERI BLEBER 1 PRAMBANAN SLEMAN - Canggih Kharisma; Suyatno Suyatno (Universitas Ahmad Dahlan, 2018)
This study aims to describe the planting of Discipline character in Bleber 1 Prambanan Sleman Elementary School, which includes the value of disciplinary characters instilled in the school. Student discipline is formed because of the teacher's leadership role that appropriately applies discipline in school. The teacher also has a role as a role model in implementing discipline. This study included qualitative descriptive research. The research subjects were principals, teachers, and students. The object of research is the role of the teacher in instilling student discipline. The technique of collecting data through interviews, observation, and documentation. The data analysis technique uses the Miles and Huberman models which include data reduction, data presentation, and conclusion drawing. The results of the study showed that the planting of the character of the discipline of students at Bleber 1 Elementary School in Prambanan Sleman was well-created. The role of the teacher in instilling student discipline is as a role model and motivator. As a role model the teacher gives an example to students and as a motivator the teacher always gives advice to students. Supporting factors in instilling discipline in the form of giving gifts as appreciation and punishment as sanctions are very instrumental in regulating the pattern and behavior of students so that they are always orderly in carrying out a discipline. The inhibiting factor in instilling discipline comes from students' internal factors. Discipline is important in order to create a comfortable and safe learning environment in schools.